2022
DOI: 10.3390/genes13010102
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Origin of the RSPO2 Long-Hair Allele and Epistatic Interaction between FGF5 and RSPO2 in Sapsaree Dog

Abstract: Genetic analysis of the hair-length of Sapsaree dogs, a Korean native dog breed, showed a dominant mode of inheritance for long hair. Genome-Wide Association Study (GWAS) analysis and subsequent Mendelian segregation analysis revealed an association between OXR1, RSPO2, and PKHD1L1 on chromosome 13 (CFA13). We identified the previously reported 167 bp insertion in RSPO2 3’ untranslated region as a causative mutation for hair length variations. The analysis of 118 dog breeds and wolves revealed the selection si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“… 13 However, our study indicated that Sapsaree is more closely related to Tibetan Mastiff and Siberian Husky than to Tibetan Terrier and Lhasa Apso, which is also supported by the higher haplotype sharing of dog leukocyte antigen class II genes between Sapsaree and Tibetan Mastiff than that between other breeds. 20 Recently, we reported that the 167 bp repeat sequence insertion in the RSPO2 3′ UTR, which is identical to the previously reported mutation for furnishing, is responsible for the long hair phenotype of Sapsaree, and the hair length-related RSPO2 mutation is identical across all modern dog breeds with long hair. 20 This is consistent with our result that predicted the admixture between the Tibetan Terrier and Sapsaree in the Treemix analysis ( Figure 2 A).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“… 13 However, our study indicated that Sapsaree is more closely related to Tibetan Mastiff and Siberian Husky than to Tibetan Terrier and Lhasa Apso, which is also supported by the higher haplotype sharing of dog leukocyte antigen class II genes between Sapsaree and Tibetan Mastiff than that between other breeds. 20 Recently, we reported that the 167 bp repeat sequence insertion in the RSPO2 3′ UTR, which is identical to the previously reported mutation for furnishing, is responsible for the long hair phenotype of Sapsaree, and the hair length-related RSPO2 mutation is identical across all modern dog breeds with long hair. 20 This is consistent with our result that predicted the admixture between the Tibetan Terrier and Sapsaree in the Treemix analysis ( Figure 2 A).…”
Section: Discussionsupporting
confidence: 70%
“… 20 Recently, we reported that the 167 bp repeat sequence insertion in the RSPO2 3′ UTR, which is identical to the previously reported mutation for furnishing, is responsible for the long hair phenotype of Sapsaree, and the hair length-related RSPO2 mutation is identical across all modern dog breeds with long hair. 20 This is consistent with our result that predicted the admixture between the Tibetan Terrier and Sapsaree in the Treemix analysis ( Figure 2 A). The low population differentiation ( F ST ) among the native Korean breeds suggests gene flow among native Korean dog breeds or they were not isolated.…”
Section: Discussionsupporting
confidence: 70%
“…From the comparison of longhaired and shorthaired subjects, the latter composing 17% of the sample, we identified RSPO2, a gene known to be responsible for the presence of furnishing and wire hair in the canine species [20]. Moreover, the evidence of different combination of mutations in RSPO2 and FGF5 associated with the longhair phenotype in several dog breeds suggests an epistatic interaction between the two and, thus, that RSPO2 plays a role in the determination of the hair length in this species [20][21][22]. CREM, another gene we identified, is involved in the regulation of AP-1 [23], a dimer of FOS and JUN that seems to regulate the composition of dog undercoat [24].…”
Section: Discussionmentioning
confidence: 81%